Genus and Genre: The Old French Verse Roman d'Alexandre, Alexander and Dindimus, and MS Bodl. 264. (May 2015) - Gilbert, Jane
Abstract : This essay argues that genres as positive entities are fantasies that texts project, and proposes to study how such projection occurs. Drawing on Derrida's account of genre as law, it explores how Agamben's work on genus might extend into poetics. Through content, form, and treatment of the philosophical question of the limits of human being, three medieval artifacts, each foregrounding Alexander the Great, position themselves relative to law, and therefore to genre. By invoking two genres ( roman antique and chanson de geste ) without conforming to either, the Old French Roman d'Alexandre carves out a position at once subject to and exempted from the law. Contrastingly, the Middle English Alexander and Dindimus claims exemplary obedience to the law as the perfect alliterative debate poem. Oxford, Bodleian Library, MS Bodl. 264 treats Alexander and Dindimus as an interpolation completing the Roman d'Alexandre, adding a French prose Marco Polo and a program of illustrations. Bodl. 264 presents itself as supplementing the law when it overrides textual, formal, and linguistic boundaries in the name of Christian expansionism. In each artifact, relations to poetic laws interact with political and philosophical stances, inviting different audience responses.